Identifikasi Potensi Wisata Susur Sungai Kalimas Kota Surabaya - Nurany, Fierda; Fitriawardhani, Tira (Publiciana, 2024)
Surabaya is one of the largest cities in Indonesia, with a long history that can be developed into a tourist attraction. One of them is along the Kalimas River in Surabaya. Follow the Kalimas River in Surabaya, passing historical locations in Surabaya such as the submarine monument (MONKASEL) and passing several educational spots such as the Education Museum and Achievement Park. These things show that there is still potential for improvement in aspects of accessibility and comfort for tourists. The aim of this research is to identify the potential of the Kalimas River Basin as a tourist attraction. This is done by evaluating five main aspects of tourism development, namely attractions, accessibility, amenities, accommodation and activities. In addition, this research will analyze the factors that support or hinder tourism development in the area. The research methodology applies qualitative descriptive techniques. Strategies for collecting data include the use of observation, interviews and documentation methods. Research findings show that the potential for the Kalimas River Tour as a tourism attraction appears to be large, especially with the integration of historical, cultural and culinary attractions. Improved facilities, accommodations and accessibility can further enhance the visitor experience and have a positive impact on the local economy. With good planning and responsiveness to visitor feedback, tourism along the Kalimas River can continue to develop and become a popular destination in Surabaya. not yet fully maximized, several components in tourism development still need to be improved